2018
DOI: 10.4315/0362-028x.jfp-17-270
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Hepatitis E Virus RNA in Raw Cured Sausages and Raw Cured Sausages Containing Pig Liver at Retail Stores in Switzerland

Abstract: Hepatitis E virus (HEV) is the causative agent of an acute and self-limiting hepatitis and is increasingly detected in food products containing pork. In this study, 102 raw sausages containing pig liver (mortadella di fegato) and 18 raw pork sausages (salami type sausage) collected at retail level in a region of southern Switzerland were screened for the presence of HEV by quantitative real-time reverse transcription PCR. HEV was detected in 12 (11.8%) of 102 mortadella di fegato products but not in any of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 16 publications
1
21
0
Order By: Relevance
“…Meat products were not statistically associated with HEV seropositivity but showed higher rates (>55%) (game, offal, liver, pork). These meat products have been frequently associated with higher seroprevalence or HEV RNA detection [44,45,46,47].…”
Section: Resultsmentioning
confidence: 99%
“…Meat products were not statistically associated with HEV seropositivity but showed higher rates (>55%) (game, offal, liver, pork). These meat products have been frequently associated with higher seroprevalence or HEV RNA detection [44,45,46,47].…”
Section: Resultsmentioning
confidence: 99%
“…Table 4 summarises studies that have investigated the thermal inactivation of HEV in non-food matrix samples. Inactivation condition combinations found sufficient to (Burri et al 2014) 1.3% of 160 slaughterhouse livers (Müller et al 2017) 11.8% of 102 raw liver sausages (Giannini et al 2017) 11.7% of 90 pork liver and raw meat sausages (Moor et al 2018) UK 92.8% of 629 pigs, with 20.5% viraemic at slaughter (Grierson et al 2015) 10.0% of 63 sausages, 3.0% of 40 slaughterhouse livers (Berto et al 2012) USA 21.9% of 182 pigs (Owolodun et al 2013) 11.0% of 127 retail liver (Feagins et al 2007) inactivate virus in these studies are shown in Fig. 3.…”
Section: Hev In Pigs and Pork Productsmentioning
confidence: 99%
“…71 Outbreaks involving viruses on game meat have been reported. 72,73 Mortadella di fegato-type sausages made with raw pig liver were identified as a potential source of HEV infection in humans. 73 The occurrence and viral load of HEV in raw mortadella de fegato sausages (air-dried sausages containing pig liver) and raw pork sausages (salami-type sausages) in Switzerland was assessed.…”
Section: Safety Of Fermented Sausages From Game and Venisonmentioning
confidence: 99%
“…72,73 Mortadella di fegato-type sausages made with raw pig liver were identified as a potential source of HEV infection in humans. 73 The occurrence and viral load of HEV in raw mortadella de fegato sausages (air-dried sausages containing pig liver) and raw pork sausages (salami-type sausages) in Switzerland was assessed. 73 It was found that 11.8% of the mortadella de fegato sausages (n = 102) were contaminated, whereas no HEV was detected in the salami sausages (n = 18).…”
Section: Safety Of Fermented Sausages From Game and Venisonmentioning
confidence: 99%